Analysis of Factors Associated with the Incidence of Depression in Children with Diabetes - Hotma Rumahorbo; Lia Herliana; Atin Karjatin (Alliance oh Health Activists (AloHA), 2021)
Diabetes is a serious problem in both developed countries especially in developing countries. The impact of disease is not only on organ damage but also on psychological-social conditions. Children with diabetes can experience low self-esteem, feel isolated and discriminated against by their environment of which will lead to depression and even suicide (attempted suicide). The aim of the study is to identify the factors that contribute to the incidence of depression in children. Analytical research design with cross sectional approach. The sample consisted of 41 children with diabetes in West Java. the results of 23 respondents (56.1%) did not experience depression and 18 respondents experienced depression (43.9%). From the incidence of depression, 23 respondents (56%) had more female sex, 25 people (61%) of age 7-13 years (61%), 90% of primary education and the most duration of illness was in the range 1 - 5 years 53.7%. The results of statistical testing on the relationship between risk factors in this case gender, child's age, children's education, duration of illness and age at initial diagnosis of DM with the incidence of depression all factors have no significant relationship. For further research, it is hoped that the coverage area will be wider so that the samples are more and more representative. Keywords: depression; gender; age of children; education; duration of illness